MUTATION OF SERINE-83 TO PHENYLALANINE AND TYROSINE IN THE GYRA GENE OF FLUOROQUINOLONE-RESISTANT SALMONELLA ENTERICA SEROVAR TYPHI ISOLATES FROM FUNTUA, NIGERIA - Ojo, Rotimi Johnson; Lawal, Abdulhakeem; Anunobi, Oluchukwu Ogechukwu; Makolo, Daniel (FUDMA Journal of Sciences, 2026)
Mutation in quinolone resistance determining region of Salmonella enterica serovar typhi are mostly associated with fluoroquinolone resistance and typhoid fever treatment failure. This study aims to identify chromosomal mutations in DNA gyrase gene of Salmonella enterica serovar Typhi as possible mechanism of fluoroquinolone resistance in patients that are completely resistant to ciprofloxacin, levofloxacin and ofloxacin in Funtua Primary Health, Katsina State.139 stool samples of patients with history of recurring typhoid fever that tested positive to Widal tests were collected and used for this research. Salmonella typhi identification was performed using standard microbiological and biochemical procedures while antibiotic susceptibility testing was performed by Kirby-Bauer disc diffusion method. The gene of the isolates with complete resistance to the three drugs were extracted for identification of chromosomal mutations in DNA gyrase gene. The results of the biochemical test confirmed 96(69.06) samples to be positive with the most prevalence seen among 16 – 45years and more positive isolates among the male. Fluoroquinolone susceptibility testing showed that 67 (69.79%) isolates were resistant to a single fluoroquinolone, 27 (28.13%) exhibited resistance to two while 2 (2.08%) were completely resistant to all the three fluoroquinolones tested. Among the three drugs tested, the most prevalent antibiotic resistance was to Ofloxacin. Molecular analysis of gyrase A showed mutation of serine-83 to phenylalanine and tyrosine respective in the two resistance samples. Given that fluoroquinolones remain first-line therapy for typhoid fever caused by S. Typhi in developing countries, decreased susceptibility may pose a threat to the disease management in this area.